2021
DOI: 10.1186/s41935-021-00239-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and comparison of population genetics software in Rabari Tribe of Gujarat population

Abstract: Background Today, when forensic experts talk about quantifiable hereditary traits, they do not just depend on the assessment and examination of DNA profiles but also relate them to the population structures. The use of high-throughput molecular marker technologies and advanced statistical and software tools have improved the accuracy of human genetic diversity analysis in many populations with limited time and resources. The present study aimed to investigate the genomic diversity in Gujarat’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…These results are similar to the results of the study of Abdul-Khalek (2017), which found that happiness and self-esteem predict the quality of life. It is also similar to the results of Mishra's (2014) study, which found that optimism predicted quality of life. The quality of life is affected by a person's view on life in general and his vision of the future in particular.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to the results of the study of Abdul-Khalek (2017), which found that happiness and self-esteem predict the quality of life. It is also similar to the results of Mishra's (2014) study, which found that optimism predicted quality of life. The quality of life is affected by a person's view on life in general and his vision of the future in particular.…”
Section: Discussionsupporting
confidence: 90%
“…Allelic frequency data obtained from the unrelated individual in a population is essential. It is the key to obtain reliable results in an analysis of DNA profiles [12]. Specificity of Short tandem repeat (STR) genetic locus is highly polymorphic repeat sequences.…”
Section: Introductionmentioning
confidence: 99%